HUBUNGAN ANTARA DISIPLIN, TANGGUNG JAWAB DAN MINAT BELAJAR DENGAN PEMEROLEHAN BELAJAR ILMU PENGETAHUAN SOSIAL PESERTA DIDIK SEKOLAH DASAR - Ari, Ari; Marzuki, Marzuki; Sulistyarini, Sulistyarini (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
Abstract:This study aimed to describe : 1).Discipline, 2).Responsibility, 3).Learning Interests, 4).acquisition of Social Science lesson. The method used is descriptive with quantitative approach. The type of research is correlational (relationship). Data analysis technique used statistical descriptive analysis assisted by SPSS program 17. The tool used is questionnaires and documentation daily test scores. The study was conducted in Grade V of primary school 17 Kubu Raya. Subjects of the study participants amounted to 52 people. Result of research: 1).discipline with Social Science learning achievement obtained r counte > r table or 0.682>0.271 at 5% significant level. 2).responsibilities with Social Science learning achievement obtained r counte > r table or 0.733>0.271 at 5% significant level. 3).interest in learning with Social Science learning achievement obtained r counte > r table or 0.750>0.271 at 5% significant level. 4). discipline, responsibility and interests learning in together with the learning achievement obtained r counte > r table or 26.125>2.80 at 5% significant level. Conclusion: 1).there is a significant correlation between discipline and learning achievement, 2).there is a significant correlation between responsibility and learning achievement; 3).There is a significant correlation between interest learning and learning achievement 4).There is a significant correlation between discipline, responsibility and interests learning in together with the learning achievement.Â Keywords: Discipline, Responsibility, Interest Learning and Learning Achievement